Respostas

2014-06-28T16:15:24-03:00
10  + 8   = 4
x+2  x+1

10(x+1) + 8(x+2)= 4(x+2)(x+1)
        (x+2)(x+1)

10(x+1) + 8(x+2)= 4(x+2)(x+1)
10x+10+8x+16=4(x²+x+2x+2)
18x+26=4x²+12x+8
4x²+12x+8=18x+26
4x²+12x-18x+8-26=0
4x²-6x-18=0

Δ = b2 - 4.a.c 
Δ = -6² - 4 . 4 . -18 
Δ = 36 - 4. 4 . -18 
Δ = 324

x = (-b +- √Δ)/2a
x' = (-(-6) + √324)/2.4         x'' = (-(-6) - √324)/2.4
x' = 24 / 8                         x'' = -12 / 8
x' = 3                                x'' = -1,5

Substitua os valores encontrados e vai dar 4 como resposta. 
1 5 1
A melhor resposta!
2014-06-28T16:29:41-03:00
     10       8     = 4
x + 2          x + 1

0 m.m.c será (x+2) .(x+1)

10.(x+1)      +     8 . (x+2)       =  4.(x+2).(x+1) 
(x+2).(x+1)        (x+2).(x+1)        (x+2).(x+1)

10(x+1) + 8.(X+2) = 4.(x+2).(x+1)
10x+10 +8x+16= 4. (x² +x +2x +2)
18x + 26= 4x² +4x +8x +8
-4x² +18x -4x -8x = 8 -26
-4x² +18x -12x= - 18
-4x² + 6x +18=0
a= -4    b= 6    c=18

Δ= b² -4.a.c
Δ= (6)² -4.(-4).18
Δ= 36 + 288
Δ=324

x= -b +- √Δ
         2.a
x= - 6 +- √324
           2.(-4)
x= -6 +- 18 
         -8
x'= -6 - 18 = -24 = 3
         -8         -8

x"= -6 + 18  = 12   = - 3 
            -8        -8        2

S= { -3/2 ; 3 }
2 5 2